PERILAKU DAN GAYA BELAJAR DENGAN PRESTASI MAHASISWA SEMESTER IV JALUR UMUM TAHUN AKADEMIK 2013/2014 JURUSAN KEBIDANAN POLITEKNIK KESEHATAN KEMENKES KUPANG TAHUN 2013 DI KUPANG - MARIANA NGUNDJU AWANG (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2014)
Learning is a human necessary and need to be done, because without learning human wouldn’t have knowledge.All human being are learning but the diffeerecies between one and each other is how they learn. Every people have they own style to learn because their ability of each individual are not the same. Nasution said that not everyone follows the same way, each show the differences, and learning styles related to personal of people, and affected by the development of education and history of human being. The fact is almost all the student was not active in learning process, there is not dialogue between student and lecture it makes a tendency of implementation teacher center method and only transfer of knowledge. Student have tendency to only relying handout from lecturer, don’t have handbook. Whereas learning was a personal activity. Activities conciousely choosen deliberately because someone has a certain individual goals. So activities of student really needed on learning process. This greatly affects the Performance Assessment of student learning at the end of the semester/end of the program, namely the requirement that a minimum Grade pass should be 2.75.